Upregulation of BIRC5 plays essential role in esophageal squamous cell carcinoma - Zu-Xuan Chen (AIMS Press, 2021)
Background: Esophageal squamous cell carcinoma (ESCC) is one of the most common cancers in the world, the detection and prognosis of which are still unsatisfactory. Thus, it is essential to explore the factors that may identify ESCC and evaluate the prognosis of ESCC patients.